Prophet Muhammad the last messenger of Allah swt - Nor Azlin Japar; Norul Azila Arifin (2013)
This book takes readers through the life of Prophet Muhammad saw. We will read about his life, from his childhood years as an orphan to his years as a Prophet and Allah's messenger